Spectroscopic Studies on Ti3+-Doped Na2O-PbO-Al2O3-B2O3-SiO2 Glasses (Global Journal of Science Frontier Research, 2020)
Na 2 O-PbO-Al 2 O 3 -B 2 O 3 -SiO 2 glasses doped with different concentrations of TiO 2 (ranging from 0 to 0.9 mol %) in steps of 0.3 mol % is synthesized by melt quenching method. The samples are characterized by X-ray diffraction (XRD), the powder XRD pattern of all the prepared samples con firms the amorphous nature of the glass. Thermal an alysis has been carried out for the prepared glasses, their glass transition temperature (T g ) and crystallization temperature (T c ) are evaluated using their Differential thermal analysis (DTA) profiles. Optical absorption and Fourier transform infrared (FT-IR) spectroscopic techniques have been studied. The UV-Vis absorption spectra of these glasses exhibit two resolved bands at about 691 nm and 832 nm due to 2 B 2g → 2 A 1g and 2 B 2g → 2 B 1g transitions of Ti 3+ ions. From the absorption spectra, the optical band gap and Urbach energies are evaluated. The FT-IR spectra has been carried out the existence of conventional and structural units of these prepared glasses. Various physical parameters and optical basicity are also evaluated with different concentrations of TiO 2 ions.
Keywords: optical absorption; FT-IR; XRD; DTA analysis; physical parameters